2014
DOI: 10.1007/s11104-014-2027-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of small-scale processes in the rhizosphere of Lupinus albus using micro push-pull tests

Abstract: Background and Aims Rhizosphere processes affect the mobility, phytoavailability and toxicity of solutes in soil. To study reactions in the rhizosphere under quasi in situ conditions, we recently developed the "micro push-pull test" (μPPT) method, combining micro-suction cups with the principle of the "push-pull test" method known from groundwater applications. Here we report the application of μPPT to investigate rhizosphere reactions in situ, i.e. degradation of deuterated citrate (citrate-d4) in the rhizosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Carboxylate exudation rates appeared to be extremely low, probably because the 20 h collection period was too long: repeated sampling on eight additional plants showed that carboxylate concentrations decreased after 40-120 min ( Fig. S1), probably as a result of declining exudation or microbial breakdown (Knecht et al, 2014;Valentinuzzi et al, 2015). In addition, plants were becoming senescent after 12 wk of strong P deficiency.…”
Section: Carboxylate Exudation (Expt 2)mentioning
confidence: 99%
“…Carboxylate exudation rates appeared to be extremely low, probably because the 20 h collection period was too long: repeated sampling on eight additional plants showed that carboxylate concentrations decreased after 40-120 min ( Fig. S1), probably as a result of declining exudation or microbial breakdown (Knecht et al, 2014;Valentinuzzi et al, 2015). In addition, plants were becoming senescent after 12 wk of strong P deficiency.…”
Section: Carboxylate Exudation (Expt 2)mentioning
confidence: 99%